Effectiveness of eight weeks pencil push up therapy for patients with convergence insufficieny in RSMH Ophthalmology Clinic Palembang - Andrian Suner; Linda Trisna; Erial Bahar (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Background : Convergence Insufficiency (CI) is an inability to perform convergence movements when doing near activity. The prevalence of CI was estimated varying between 0.1%-8%. One of the easiest therapeutic attempts from some research have showed the effectiveness to overcome CI is by pencil push up therapy. This study is to determine the improvement of CI symptoms and signs in patients after performing the pencil push up exercise for 8 weeks. Methods: This clinical trial was conducted on October 2016 until March 2017. Nineteen patients who met the inclusion criteria was obtained. The frequency and distribution of data is described in tabular form and the effectiveness of pencil push up therapy is analyzed with Paired T Test and Wilcoxon test. Result: Patients with CI had an average age of approximately 22 years, with the sex ratio of females and males being 3:2. After 8 weeks of pencil push up therapy, there was a significant decrease of Convergence Insufficiency Symptom Survey (CISS) value from 25.2±3.72 to 15.7±5.64 (p=0.000), significantly decreased Near Point Convergence (NPC) value from 13.7±1.88 cm to 9.05±2.99 cm (p=0.000), significantly decreased Red Blue Test (RBT) value from 14.2±1.84 to 9,36±3.22 cm (p=0.000), and significantly decreased Penlight Red/Green Test (PLT) from 16.7±2.69 to 10.7±4.13 cm (p=0.000). A number of Alternate Cover Test (ACT) positives also decreased from 4 to 2 samples but not significant (p=0,500). Symptoms and signs of CI were improved in 14 samples (73.7%). Conclusion : Pencil push up therapy for 8 weeks is effective to improve symptoms and signs of convergence insufficiency.